2018
DOI: 10.1021/acs.organomet.8b00071
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Dependent Hemilability of (2-Diphenylphosphino)Phenol in a Ru(II) para-Cymene System

Abstract: The addition of Ph2P­(2-C6H4OH) to [(η6-p-cymene)­RuCl­(μ-Cl)]2 led to the formation of three distinct products, depending on the experimental conditions. The previously reported [(η6-p-cymene)­RuCl­{κ2 P,O-PPh2(2-C6H4O)}], 1, was obtained in 90% yield using MeOH as the solvent, in the presence of a base (Et3N). Conversely, [(η6-p-cymene)­RuCl­{κ2 P,O-PPh2(2-C6H4OH)}]­Cl, [2]­Cl, was afforded (88% yield) in MeOH without using the base. However, [(η6-p-cymene)­RuCl2{κP-PPh2(2-C6H4OH)}], 3, was the major species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 105 publications
1
7
0
Order By: Relevance
“…Dynamics have been shown to influence not only enzyme chemistry but also homogeneous catalysis where structural flexibility has been linked to enhanced activity. [22][23][24][25][26][27][28][29][30] Similar arguments have also been made in the case of single-site heterogeneous catalysts. 31 In supported metal catalysis, the rapid dynamics of metal clusters has also been shown to generate short-lived highlyactive species that are thought to dominate catalysis.…”
Section: Introductionsupporting
confidence: 65%
“…Dynamics have been shown to influence not only enzyme chemistry but also homogeneous catalysis where structural flexibility has been linked to enhanced activity. [22][23][24][25][26][27][28][29][30] Similar arguments have also been made in the case of single-site heterogeneous catalysts. 31 In supported metal catalysis, the rapid dynamics of metal clusters has also been shown to generate short-lived highlyactive species that are thought to dominate catalysis.…”
Section: Introductionsupporting
confidence: 65%
“…Phenolic phosphines such as Ph 2 PC 6 H 4 OH have been used either natively or with chain extenders such as triethylene glycol to enhance solubility for a ruthenium complex for catalysis in water . The confinement of triarylphosphines in microenvironments leading to enhanced performance of catalytic processes as well as a number of studies aimed at enhanced anticancer activity also of ruthenium complexes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…12 1 + X, +Y, +Z; 13 X, Y, 1 + Z. Notes: Calculated by Mercury CSD (using Bondi van der Waals radii).…”
mentioning
confidence: 99%
“…[22] Furthermore, bridge cleavage reactions of metal dimers with P/N-chelating ligands in CH 3 OH have been shown to afford analogous P/N-chelate complexes. [23,24] On this basis we tentatively suggest formation of intermediate B whereby 1 coordinates through both P/N amine donor centres. This is supported by our observation that 1 can behave similarly, as found in [Pt(CH 3 )Cl(P,N-1)] 4, which is readily accessible from [Pt(CH 3 )Cl(η 4 -cod)] and 1.…”
Section: Synthesis and Reactivity Of Complexes Withmentioning
confidence: 60%